2022
DOI: 10.3390/app12199983
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Selected Quality Indices in Microbially Fermented Commercial Almond and Oat Drinks

Abstract: (1) Background: Interest in plant analogues for food of animal origin is increasing. There are some pro-healthy food ingredients, such as odd-chain, cyclic, and branched fatty acids, that are perceived to be characteristic for food of animal origin or fermented. The purpose of the present study was to determine whether commercial plant drinks can be valuable nutrient mediums for the multiplication of lactic acid bacteria and yeasts. The goal was also to determine their potential for the production of the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Yeasts generally can utilize sugars and lipids as carbon sources, while LAB primarily utilize various sugars for carbon utilization. Grzegorz Dąbrowski and colleagues [ 49 ] outlined the advantages of fermenting oats with a yeast strain— Yarrowia (Y) lipolytica YLP 0001. The study found that Y. lipolytica YLP 0001 fermentation increased acidity, characterized by higher levels of dissociated acids (such as lactic, citric, and succinic acids) and undissociated acids (such as amino acids and fatty acids).…”
Section: Methods Employed To Produce Fermented Oatsmentioning
confidence: 99%
“…Yeasts generally can utilize sugars and lipids as carbon sources, while LAB primarily utilize various sugars for carbon utilization. Grzegorz Dąbrowski and colleagues [ 49 ] outlined the advantages of fermenting oats with a yeast strain— Yarrowia (Y) lipolytica YLP 0001. The study found that Y. lipolytica YLP 0001 fermentation increased acidity, characterized by higher levels of dissociated acids (such as lactic, citric, and succinic acids) and undissociated acids (such as amino acids and fatty acids).…”
Section: Methods Employed To Produce Fermented Oatsmentioning
confidence: 99%
“…Yeasts, mainly used in baking and brewing (wine, beer, bread fermentation), dominate the microbial composition of many alcoholic food fermentations [ 49 ]. In general, LABs utilize various sugars as carbon sources while yeasts can utilize both sugars and lipids [ 50 ]. Saccharomyces cerevisiae, especially C. lipolytica and Y. lipolytica , is an effective producer of lipases and proteases [ 30 , 34 ], allowing for proteins and lipids to be hydrolyzed more quickly to amino acids and fatty acids.…”
Section: Strainsmentioning
confidence: 99%
“…The highest content of minor fatty acids was determined in oat beverages fermented by L. plantarum PK 1.1 and Kluyveromyces marxianus KF 0001. Among the used strains, Yarrowia lipolytica YLP 0001 was found to be a major producer of aromas and lactic acid in these two beverages, suggesting that the strain can utilize various carbon substrates [ 50 ]. Lavinia Florina Călinoiu et al evaluated the potential of Saccharomyces cerevisiae ( S. cerevisiae ) fermentation in increasing the phenolic acid content and composition, and the antioxidant activity of commercial wheat bran (WB) and oat bran (OB).…”
Section: Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers choose these beverages as alternatives to dairy milk due to health, environmental, and lifestyle preference reasons. Plant-based beverages that are also known as non-dairy milk substitutes are popular for their taste, nutrient value, including vitamins, low-fat content, and ethical advantage, as well as related dietary and environmental aspects [ 2 , 3 ]. Investments are currently being made toward the further development and production of such products in order to refine the technology and improve the nutritional value of plant-based drinks, as well as improve their taste and extend their shelf-life [ 1 ].…”
Section: Introductionmentioning
confidence: 99%